Sociodemographic profile, contraceptive practice & awareness of HIV infection among unmarried postpartum women in a tertiary centre in Malaysia - Mustafa, Kamarul Bahyah; Ibrahim, Norliza; Abdul wahab, Noraziana; Abdullah, Suhaiza; Awang, Mokhtar (Faculty of Medicine, International Islamic University Malaysia, 2014)
Introduction: To describe the sociodemographic profile, contraceptive practice, and awareness of HIV infection among unmarried post partum women in the biggest government hospital in Pahang. Methods: A cross sectional questionnaire-proforma-based study was conducted for one year duration from August 2010 until July 2011 by identifying and recruiting all the unmarried women upon admission for delivery. Basic information were obtained from the use of patients’ case notes, and further related and necessary information were obtained from a direct face-to-face interview based on a proforma. Results: A total of 121 unmarried women were identified and recruited. The age ranged from 13 to 36 years with a mean age of 21.6 years. 31.4% were teenagers. Only 16% of patients have tertiary education, and 2.5% never had any formal education. About one third of the women were smokers or ex-smokers, 7.5% had consumed alcohol, but none denied ever use of any recreational drugs. Almost 9% has prior history of being sexually assaulted. About three quarter of the women never used any contraceptive method. Majority of the patients (85.1%) were aware of HIV transmission risk; 75% never had any antenatal checkup or booked at late gestation (> 20 weeks); and 45.8% were not aware of any support groups for single mothers. Conclusion: Single unmarried women are associated with disadvantaged sociodemographic profile. Contraceptive practice was also very low despite significant awareness towards risk of HIV infection. Further follow up, support and care should be offered to these women. KEYWORDS: unmarried mothers, unwanted pregnancies, sociodemography, HIV awareness, contraceptive use